2013
DOI: 10.1177/1043659613514114
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs Related to Salt-Restricted Diet in Patients on Hemodialysis

Abstract: Nurses are recommended to make tailored interventions by taking the benefits and barriers that the patients perceive toward low-salt dietary adherence into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…In this study, two of the most frequently identified barriers were "food does not taste good on a low-salt diet" and "following a low-salt diet is hard to do when I go out to eat." Our findings are congruent with previous studies (Agondi et al, 2011;Kara, 2014;Walsh & Lehane, 2011;Welch et al, 2006), reporting that tailored interventions are necessary to change these two beliefs. It should therefore be emphasized to the patients that "a low-salt diet does not mean tasteless food" (Charra & Chazot, 2003, p. 345), and it takes some time to adapt to a low-salt diet (World Health Organization, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, two of the most frequently identified barriers were "food does not taste good on a low-salt diet" and "following a low-salt diet is hard to do when I go out to eat." Our findings are congruent with previous studies (Agondi et al, 2011;Kara, 2014;Walsh & Lehane, 2011;Welch et al, 2006), reporting that tailored interventions are necessary to change these two beliefs. It should therefore be emphasized to the patients that "a low-salt diet does not mean tasteless food" (Charra & Chazot, 2003, p. 345), and it takes some time to adapt to a low-salt diet (World Health Organization, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The mean perceived benefits score of our sample was 28.03 (item M = 4.00, SD = 0.76), which was similar to that of patients on HD in the United States (27.20 ± 2.66;Welch et al, 2006), in Brazil (4.0 ± 0.6;Agondi et al, 2011) and in another study in Turkey (28.0 ± 4.0; Kara, 2014). The mean perceived barriers score was 11.43 (item M = 2.29, SD = 2.20), which was lower than that reported by Welch et al (2006;13.10 ± 2.99), Agondi et al (2011; 3.0 ± 0.5) and Kara (2014; 12.9 ± 3.6). Our findings suggest that the item mean perceived benefit score was higher than the item mean perceived barrier score.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations